A Marxist history of the world : from Neanderthals to Neoliberals - Faulkner, Neil (Counterfire (Series), 2013)
This magisterial analysis of human history combines the insights of earlier generations of Marxist historians with radical new ideas about the historical process. Reading history against the grain, Neil Faulkner reveals that what happened in the past was not predetermined. Choices were frequent and numerous. Different outcomes - liberation or barbarism - were often possible. Rejecting the top-down approach of conventional history, Faulkner contends that it is the mass action of ordinary people that drives great events. At the beginning of the 21st century - with economic disaster, war, climate catastrophe and deep class divisions - humans face perhaps the greatest crisis in the long history of our species. The lesson of A Marxist History of the World is that, since we created our past, we can also create a better future.